Efficient Degradation of Methylene Blue Using La-PTC-HIna/Ti3C2Tx MXene: Adsorption and Photocatalytic Degradation - Agustino Zulys; Adawiah Adawiah; Nasruddin Nasruddin (Indonesian Journal of Chemistry, 2022)
Isonicotinic acid is a pyridine carboxylic compound that can be used as a linker to construct coordination complexes. Adding isonicotinic acid (HIna) to the metal-organic framework (MOF) enhanced the MOF surface area, pore volume, and pore size and increased its catalytic activity. Ti3C2Tx MXene nanosheet with excellent metal conductivity was also employed on MOF to optimize its functionality. This work aims to synthesize MOF modulated isonicotinic acid La-PTC-HIna and design the new materials: La-PTC/Ti3C2Tx MXene and La-PTC-HIna/Ti3C2Tx MXene hybrid, then apply them for methylene blue photodegradation. La-PTC-HIna, La-PTC/Ti3C2Tx MXene, and La-PTC-HIna/Ti3C2Tx MXene were synthesized by the sonochemical method. MOF La-PTC-HIna has the highest methylene blue photocatalytic degradation activity than MOF La-PTC, Ti3C2Tx MXene, La-PTC/Ti3C2Tx MXene, and La-PTC-HIna/Ti3C2Tx MXene with degradation efficiency of 99.48% in 20 ppm methylene blue under visible irradiation for 210 min. This study reveals the La-PTC-HIna and La-PTC-HIna/Ti3C2Tx MXene as a new material that has the potential to remove methylene blue from an aqueous solution.